Hubungan Peran Biokimia dalam Pengolahan Makanan Fungsional - Septi Puspita Kurniawati; Pramai Sheila Eka Khoireina; Azlinatul Lulu Kharolaini; Elsa Oktavia Ramadhani; Liss Dyah Dewi Arini (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This study aims to examine the role of biochemistry in the processing of functional foods and its impact on the nutritional content and bioactive compounds. The method used is a literature review, collecting and analyzing relevant literature on biochemistry, food processing, and functional foods. The results show that biochemical processes, such as fermentation and heating, can affect the nutritional content of food. Fermentation can increase the content of probiotics and unsaturated fatty acids that are beneficial for health, while excessive heating can damage sensitive compounds like vitamin C. Proper processing can enhance the bioavailability of bioactive compounds, thus optimizing the health benefits of functional foods. The conclusion of this study emphasizes the importance of understanding biochemical processes in food processing to maximize health benefits.